A PHILOSOPHER WORKS FROM HOME: DIARIES OF A PHILOSOPHICAL ROMP THROUGH VAST TERRITORIES, SOMETIMES CROSSING OVER INTO UNCHARTED REGIONS OCCUPIED BY OTHER PEOPLE. Issue 57 (2021) - Thalos, Mariam
ABSTRACT: This is my impersonation of a philosopher working from home, which aims at making lively a few worthy philosophical questions. The old is new again, as each generation confronts its own challenges and demons, in its own context.